2004
DOI: 10.1177/112972980400500104
|View full text |Cite
|
Sign up to set email alerts
|

ProCol® Vascular Bioprosthesis for Vascular Access: Midterm Results

Abstract: Our midterm results demonstrated that the ProCol vascular bioprosthesis was a promising material for VA with good patency and low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…15 Other biological grafts such as bovine mesenteric vein and depopulated ureters also have substantial rates of dilatation. 8,11 By contrast, we recorded no true aneurysms in the implanted vessels at any time. The small perigraft haematomas or pseudoaneurysms we report were probably cannulation site injuries caused by needle access, and are consistent with all forms of both prosthetic and autogenous vascular access.…”
Section: Discussionmentioning
confidence: 52%
“…15 Other biological grafts such as bovine mesenteric vein and depopulated ureters also have substantial rates of dilatation. 8,11 By contrast, we recorded no true aneurysms in the implanted vessels at any time. The small perigraft haematomas or pseudoaneurysms we report were probably cannulation site injuries caused by needle access, and are consistent with all forms of both prosthetic and autogenous vascular access.…”
Section: Discussionmentioning
confidence: 52%
“…As was widely described, brachial arteries are usually used in the arteriovenous hemodialysis access confection [23]. According to the findings reported in this study, the viscoelastic differences were associated with structural variations that could be involved in the origin of the intimal hyperplasia and the vascular access dysfunction.…”
Section: Discussionmentioning
confidence: 66%
“…Most retrospective studies suggest that ePTFE grafts are superior to bovine artery grafts because the former are associated with less infection and thrombosis and have a longer patency period 129–144. Decellularized xenografts made from bovine mesenteric veins145148 or bovine ureters149,150 have become available recently. Some clinical studies have suggested that these new bovine grafts may offer a safe alternative to patients who have a history of failed ePTFE grafts, but data are very limited 145.…”
Section: Prevention Strategiesmentioning
confidence: 99%